Moodle platform and Zoom videoconference: learning skills in the virtual modality - Laberiano Andrade-Arenas; William Wilfredo Reyes Perez; Cesar Augusto Yactayo Arias (Institute of Advanced Engineering and Science, 2023)
In Peruvian Universities, most of the Moodle platforms and the Zoom videoconference were used in virtual teaching-learning. The teachers and students of the University of Sciences and Humanities, which is the object of study, used these tools in the class session. Moodle and Zoom complement each other for virtual classes during the pandemic time. The objective of the research is the influence of Zoom and Moodle on learning skills. The methodological design of the research has correlational scope, quantitative, non-experimental approach of cross-section. A survey was conducted of 95 students from the first cycles of the university. The instrument was validated by expert judgments with 86.3% approval. In addition, reliability was performed with Cronbach's Alpha, obtaining the value of 0.875. A p-value of 0000 was obtained as a result and the degree of correlation between Moodle and learning skills was 0.438** and Zoom with learning skills was 0.519**; determining in this way that there is a moderate positive significant correlation. It is concluded that the development of learning skills that correspond to digital skills, the communicative and cognitive part is due to the use of the Moodle platform and the Zoom videoconference in the learning sessions.